Reaching for the stars: DingTalk and the Multi-platform creativity of a 'one-star' campaign on Chinese social media. (December 2021) - Wu, Xiaoping; Fitzgerald, Richard
Abstract: This study explores mediated forms of creativity and multi-platform affordances used by Chinese social media users and producers in a 'one-star' rating campaign aimed at DingTalk, an online teaching platform. In February 2020, in response to delays to resuming in-person instruction due to the COVID 19 pandemic, DingTalk launched a new feature called ' Zaixianxuexi ' (online learning) which was then used across the country. However, users became increasingly critical of the platform and mounted a 'one-star' campaign through the Apple's App Store rating system to try to have the platform removed. In response, the producers of DingTalk released a short-animated video and promotion campaign through Weibo and Bilibili, rather than the DingTalk platform. The video literally begged users to give it more stars. Adopting a social semiotic multimodal analytical approach, we examine the mediated interaction between users and the producers of DingTalk across three Chinese social media platforms. In particular, we examine the mediated forms of creativity and technological affordances across multiple social media platforms during the three stages of the event. The analysis focuses on the creative strategies adopted by both users and the producers of DingTalk as they engaged with each other across platforms. The study highlights Chinese social media as rich spaces where technological and cultural resources are creatively co-ordinated across platforms. In situating modality within a cross-media environment, the research underscores the creativity that characterises Chinese social media within an interconnected multi-platform social media ecology.